The Effect of Carbon Emission Disclosure, Profitability, and Firm Size on Capital Market Reaction: A Moderation Study of Media Coverage - Dewi, Arfiana (Jurnal Bisnis dan Manajemen, 2024)
The purpose of this study is to investigate how the influence of carbon emission disclosure, ROA, and company size affects the capital market reaction, especially in the form of abnormal stock returns. This is important because the causal variables studied increase investor confidence and influence their investment decisions. A critical component of national economic infrastructure is the capital market system. Meanwhile the Efficient Market Hypothesis (EMH) suggests Indonesia's capital market exhibits semi-strong efficiency, corporations must fulfil environmental and social responsibilities to maintain community legitimacy. Market participants evaluate various financial metrics, including profitability ratios and organizational scale, which significantly influence equity valuations. This research examined 42 entities within the transportation and logistics sector listed on the Indonesia Stock Exchange (IDX) during the 2021-2023 period. The finding indicates that the market has not achieved semi-strong efficiency, as investment decisions frequently demonstrate behavioural biases influenced by psychological factors rather than rational analysis. A methodological limitation of this investigation is its focus on a single sector within transportation and logistics firms.